Technological gap among Vegetable Growers - R.5. Suman, (Journal of Agricultural Extension Management, 2025)
This research study was undertaken in Kullu district of Himachal Pradesh under ex-post facto research design. A sample of 600 vegetable growers representing 20 villages of Kullu and Manali was drawn using purposive random sampling technique. The results of the study indiq1te that the technological gap was found high in seed treatment, plant protection measures, water management, hoeing and weeding, field preparation and manure and fertilizer application, while, low technological gap was observed in recommended varieties and harvesting. The overall technological gap of the respondents in respect of vegetable production technology was found to be 35 per cent. The independent variables viz. cropping intensity, infrastructural experience, education, social participation, farm size, nature of irrigation, socio-economic status, economic motivation, innovativeness, knowledge about vegetable production technology, attitude towards vegetable production technology, source of information and extension participation were found statistically significant and negatively correlated with technological gap, whereas, age did not show any relationship with technological gap